2021
DOI: 10.48550/arxiv.2110.09579
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Turning black-holes and D-branes inside out their photon-spheres

Massimo Bianchi,
Giorgio Di Russo

Abstract: Very much as extremal Reissner-Nordstöm BHs, D3-branes and their intersecting bound-states in lower dimensions enjoy a remarkable symmetry under conformal inversions that exchange the horizon with infinity and keep the photon-sphere fixed. We explore the implications of this symmetry for the dynamics of massless and massive BPS particles. In particular we find a remarkable identity between the scattering angle of a probe impinging from infinity and the in-spiraling angle of a probe with the very same energy an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…We have to numerically input l in the TBA with the boundary condition at θ → −∞: ε±,±(θ) ≃ 4P θ ≃ 4(l + 1/2)θ, also following from the asymptotic of the ODE (25) (the precision improves by adding also the constant at the subleading order). This TBA is a generalization of those found in [29,31] for the Perturbed Hairpin IM and the N f = 2 gauge theory with equal masses m 1 = m 2 respectively, although we shall pay particular attention to the change of variables from gravity or gauge to integrability: this results in n l TBA Leaver WKB 0 1 0.86814 − 0.36917i 0.86893 − 0.37286i 0.89642 − 0.36596i 0 2 1.4755 − 0.36411i 1.4778 − 0.3682i 1.4940 − 0.36596i 0 3 2.0767 − 0.36178i 2.0801 − 0.3671i 2.0916 − 0.36596i 0 4 2.6758 − 0.36007i 2.6803 − 0.3666i 2.6893 − 0.36596i (33), (through (34) with n ′ = 0) and WKB approximation (Σ1 = 0.1, Σ2 = 0.2, Σ3 = 0.3, Σ4 = 1). Since Σ1 = Σ3 the Leaver method seems not applicable (N.A.…”
Section: General Theory: Intersecting D3 Branes and Beyondmentioning
confidence: 99%
See 1 more Smart Citation
“…We have to numerically input l in the TBA with the boundary condition at θ → −∞: ε±,±(θ) ≃ 4P θ ≃ 4(l + 1/2)θ, also following from the asymptotic of the ODE (25) (the precision improves by adding also the constant at the subleading order). This TBA is a generalization of those found in [29,31] for the Perturbed Hairpin IM and the N f = 2 gauge theory with equal masses m 1 = m 2 respectively, although we shall pay particular attention to the change of variables from gravity or gauge to integrability: this results in n l TBA Leaver WKB 0 1 0.86814 − 0.36917i 0.86893 − 0.37286i 0.89642 − 0.36596i 0 2 1.4755 − 0.36411i 1.4778 − 0.3682i 1.4940 − 0.36596i 0 3 2.0767 − 0.36178i 2.0801 − 0.3671i 2.0916 − 0.36596i 0 4 2.6758 − 0.36007i 2.6803 − 0.3666i 2.6893 − 0.36596i (33), (through (34) with n ′ = 0) and WKB approximation (Σ1 = 0.1, Σ2 = 0.2, Σ3 = 0.3, Σ4 = 1). Since Σ1 = Σ3 the Leaver method seems not applicable (N.A.…”
Section: General Theory: Intersecting D3 Branes and Beyondmentioning
confidence: 99%
“…also [13,29]), that would generalize the alternative quantization condition ( 21) only if M 1 = M 2 . Moreover (38) is just the symmetry that exchange infinity (y → +∞) and the (analogue) horizon (y → −∞), leaving the photon sphere (y = 0) fixed as in [33] (thanks to identifications of certain scattering angles with the SW period). In this respect, under (38)…”
Section: General Theory: Intersecting D3 Branes and Beyondmentioning
confidence: 99%
“…In our viewpoint this intriguing correspondence could be further clarified in CFT terms, as started in [13], and other massive gravitational sources can be studied along the same lines by making use of the results of this paper. For related topics, see also [53,54,55,56,57,58].…”
Section: Introductionmentioning
confidence: 99%
“…CT transformations are known to exchange the event horizon with null infinity [6][7][8][9][10][11][12][13]. Quite remarkably, we have found that the fixed loci of the (generalised) CT transformations are precisely the photon-spheres [5], thus opening new paths to explore physical implications for QNMs and other observables such as deflection angles and time delays, coded in the so-called radial action, and ultimately on a bulk-to-boundary relation proposed in [14,15].…”
Section: Introductionmentioning
confidence: 68%
“…In [5] we have shown that D3-branes and their bound-states in lower dimensions admit a symmetry under conformal inversions that generalise the Couch-Torrence (CT) transformations known to leave the metric of extremal Reissner-Nordström BHs invariant up to a Weyl rescaling [6]. CT transformations are known to exchange the event horizon with null infinity [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%